Free margin length and coaptation surface area in normal tricuspid aortic valve: an anatomical study - De Kerchove, Laurent; Momeni, Mona; Aphram, Gaby; Watremez, Christine; Bollen, Xavier; Jashari, Ramadan; Boodhwani, Munir; Astarci, Parla; Noirhomme, Philippe; El Khoury, Gebrine (European journal of cardio-thoracic surgery, 2018)
Aortic cusp free margins are a central target in most aortic valve repair operations to optimize valve coaptation. The objective of this anatomical study was to analyse the normal dimensions of free margin length (FML) and coaptation surface and to analyse their relationship with other valve and root dimensions in normal tricuspid aortic valves. We analysed 25 aortic root homografts. Eight valve and root measurements were obtained from fresh specimens including the length of the free margin while applying appropriate tension on the structures. The valves were then fixed with formalin in the diastolic position under pressure to allow measurement of the coaptation surface. In addition to normal values, we analysed the correlations and ratios between the different measures. The mean FML was 34.3 ± 3.1 mm. The FML was similar between the 3 cusps and correlated with all other valve and root measures. The ratio of the FML to the geometric height was 1.81, and the free edge length/sinotubular junction was 1.29. The mean coaptation surface was 122 ± 21 mm2 per cusp and corresponded to 41% of the cusp surface. The central coaptation length was 3.3 ± 0.8 mm, and the lateral coaptation length was 5.9 ± 0.6 mm. The total coaptation surface per specimen was 184 ± 32 mm2. We described the normal dimensions of the FML and coaptation surface in the tricuspid aortic valve. These measurements will serve in the further development of an objective method of free margin shortening based on intraoperative measurements of the FML to treat cusp prolapse and low coaptation after valve-sparing surgery.